Empowering Recovery: Evidence-Based Social Work Interventions for Mental Health Patients in Saudi Arabia - Alkahtani, Mubarak Hozam Jery; Alotaibi, Ayidh Nashi Mater; Almurayri, Mohammed Saeed Abdullah; ALHAlF, WAFlAH NASSER; Alghamdi, Alya Jamaan Saeed; Alhamed, Shikha Fahad Saud; Hamdi, Hoda Abdullah; Alamri, Ahlam Faris Ayed; Alhumaily, Tahani Abdullah; Alharthi, Saud Saad A; Alanazi, Monifah Sulimman Radhi; Alabdulhadi, Shikha Saad (Journal of Ecohumanism, 2024)
Mental health disorders remain a significant public health challenge in Saudi Arabia, where cultural stigma and limited resources often complicate the provision of mental health services. This paper explores the role of evidence-based social work interventions in mental health recovery in Saudi Arabia, emphasizing culturally competent practices that empower patients and enhance treatment outcomes. Through a review of existing research, the paper highlights the effectiveness of interventions such as Cognitive Behavioral Therapy (CBT), psychosocial support, case management, family therapy, community-based approaches, and trauma-informed care. It also discusses the importance of integrating religious and cultural values in the therapeutic process. Ultimately, the paper advocates for a comprehensive, multi-disciplinary approach to mental health care, emphasizing the need for ongoing development of social work practice in the region.